Stability of Lactobacillus rhamnosus GG in prebiotic edible films - Soukoulis, Christos; Behboudi-Jobbehdar, Solmaz; Yonekura, Lina; Parmenter, C.D.J.; Fisk, Ian D. (Elsevier, 2014)
The concept of prebiotic edible films as effective vehicles for encapsulating probiotic living cells is presented. Four soluble fibres (inulin, polydextrose, glucose-oligosaccharides and wheat dextrin) were selected as prebiotic co-components of gelatine based matrices plasticised with glycerol and used for the immobilisation of Lactobacillus rhamnosus GG. The addition of prebiotics was associated with a more compact and uniform film structure, with no detectable interspaces or micropores; probiotic inclusion did not significantly change the structure of the films. Glucose-oligosaccharides and polydextrose significantly enhanced L. rhamnosus GG viability during air drying (by 300% and 75%, respectively), whilst a 33% and 80% reduction in viable counts was observed for inulin and wheat dextrin. Contrarily, inulin was the most effective at controlling the sub-lethal effects on L. rhamnosus GG during storage. However, in all cases the supplementation of edible films with prebiotics ameliorated the storage stability of L. rhamnosus GG.